2017
DOI: 10.1080/00207454.2017.1411353
|View full text |Cite
|
Sign up to set email alerts
|

Spatial memory recovery in Alzheimer's rat model by electromagnetic field exposure

Abstract: Our results showed that application of ELF-MF not only has improving effect on different cognitive disorder signs of AD animals, but also disrupts the processes of AD rat model formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…La estimulación con el CEM indujo a una mejoría en la prueba de giros inducidos, a pesar de que no cambió el número de neuronas dopaminérgicas en la SNc. Esto puede explicarse por otros mecanismos, como el aumento en los factores neurotróficos y la reducción del nivel oxidante, ambos como consecuencia de la estimulación magnética reportada para modelos animales de la enfermedad de Alzheimer (Akbarnejad et al, 2018) o de Huntington (Tasset et al, 2012).…”
Section: Discussionunclassified
“…La estimulación con el CEM indujo a una mejoría en la prueba de giros inducidos, a pesar de que no cambió el número de neuronas dopaminérgicas en la SNc. Esto puede explicarse por otros mecanismos, como el aumento en los factores neurotróficos y la reducción del nivel oxidante, ambos como consecuencia de la estimulación magnética reportada para modelos animales de la enfermedad de Alzheimer (Akbarnejad et al, 2018) o de Huntington (Tasset et al, 2012).…”
Section: Discussionunclassified
“…[42] There are several studies shoes LFMF benefits in killing viruses as well as enhancing the immune system functions. [43][44][45][46][47][48][49][50] In 1980s, Robach et al [56] and Cerf [57] demonstrated that ultrasonic energy can be absorbed by viruses and terminated them when use appropriately. This means viruses are sensitive to Ultrasonic energy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore; in order to gain the best results, is to use Low Frequency Magnetic Fields (LFMF) which had been tested and demonstrated by Royal Raymond Rife in 1920 [42]. There are several studies shoes LFMF benefits in killing viruses as well as enhancing the immune system functions [43][44][45][46][47][48][49][50] In 1980s, Robach et al [56] and Cerf [57] demonstrated that ultrasonic energy can be absorbed by viruses and terminated them when use appropriately. This means viruses are sensitive to Ultrasonic energy.…”
Section: Discussionmentioning
confidence: 99%